Transformasi Digital Dalam Tata Kelola Pemerintahan Desa: Upaya Menuju Smart Village di Desa Bojong Pandan Kecamatan Tunjung Teja - Ita Rosita Wahyiah (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Digital transformation in village governance is a strategic step towards creating an efficient, transparent, and participatory Smart Village. This study focuses on the application of information technology in Bojong Pandan Village, Tunjung Teja District, as an effort to improve the quality of public services and the effectiveness of village government administration. The main objective of this study is to analyze the process, obstacles, and impact of digital transformation implementation on village governance. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that the digitalization of administrative services such as population information systems, online-based correspondence archiving, and the use of social media in disseminating public information have brought significant changes to the work patterns of village officials and eased public access to services. However, obstacles remain such as limited technological infrastructure, low digital literacy among officials, and minimal public participation in utilizing available digital platforms. Efforts to increase human resource capacity through technology training, provision of a stable internet network, and collaboration with external parties are important steps towards optimizing Smart Village. In conclusion, the digital transformation in Bojong Pandan Village shows a positive direction in realizing village governance that is adaptive to technological developments, while also serving as a model for strengthening village capacity towards sustainable development based on digital innovation.